PENGARUH PENGGUNAAN MEDIA KARTUN ANIMASI TERHADAP HASIL BELAJAR SISWA KELAS VII MTs NEGERI 05 MADIUN - Suminto, Suminto (Jurnal Likhitaprajna, 2019)
The purpose of this study was to determine whether there is an influence on the use of animated cartoon media on student learning activities and outcomes. This type of research is experimental research. The research method used the one-group pretest-posttest design. This study used two research classes as an experimental class and a control class. The location of this research is MTs Negeri 05 Madiun. The subjects of the study were the eighth-grade students of MTs Negeri 05 Madiun as many as 40 people with details of 20 students as the experimental class and 20 students as the control class. The results showed that there was an influence of the Use of Animation Media on Activities and Learning Outcomes of Student on the struggle material of the Prophet Muhammad S.A.W in State MTs 05 Madiun. It could be proven that the average value of the percentage of student learning achievements in the experimental class 85.62 and 80.31 in the control class. Then the results of the t-test â‰¥ of t table 3.50 â‰¥ 2.20. Keywords: learning outcomes, animation media